IMPLEMENTASI SISTEM INFORMASI PEGAWAI (SIMPEG) BERBASIS WEB MENGGUNAKANFRAMEWORK CODEIGNITER DAN BOOTSTRAP - Dian Novianto (Jurnal Informatika Global)
Development of Information Technology is currently supporting dissemination of information quickly so that it can be accessed by mobile from anywhere and at anytime, STMIK Atma Luhur Pangkalpinang As one - the only college-based Information and Communication Technology (ICT) should also follow these developments, one system is information systems employees (SIMPEG), where the system will contain detailed information such as number of employees, history rank, history position, length of service and the other - the other, so that could be a reference material led to consider a promotion, a raise or other parts that need data employees. The system is web-based for easy access from anywhere and anytime through any device that has a browser and an internet connection and is created using CodeIgniter and Bootstrap framework, and reports can be converted into the form of a spreadsheet. The method used in this research is qualitative method in which the author is a key tool in data collection, by means of observation and interviews.Keywords:ICT, SIMPEG, CodeIgniter, Bootstrap, Qualitative